A Position Statement on Mpox as a Sexually Transmitted Disease. (22nd December 2022) - Allan-Blitz, Lao-Tzu; Gandhi, Monica; Adamson, Paul; Park, Ina; Bolan, Gail; Klausner, Jeffrey D
Abstract: The global outbreak of mpox virus constituted an international public health emergency. Reports have highlighted (1) a temporal association between sexual activity and mpox, (2) an association between specific sexual practices and location of lesion development, (3) a high frequency of sexual practices conferring risk for other sexually transmitted infections among cases of mpox, (4) that mpox virus can be isolated from sexual fluids, (4) that isolated virus is infectious, and (5) a high frequency of anogenital lesions prior to disease dissemination suggesting direct inoculation during sexual activities. Finally, a growing body of evidence suggests that sexual transmission is the predominant mode of transmission for mpox virus. We therefore conclude that mpox is a sexually transmitted disease. Labeling it as such will help focus public health interventions, such as vaccinations, testing, and treatment, as well as facilitate focused awareness and education programs toward behavioral modifications to reduce exposures. Abstract : Current evidence strongly suggests that mpox is a sexually transmitted disease. Labeling it as such will help focus public health interventions and facilitate control of the ongoing outbreak.